Poverty and Wealth in East Africa : A Conceptual History - Stephens, Rhiannon, 1977- (Book collections on Project MUSE., 2022)
"In Poverty and Wealth in East Africa Rhiannon Stephens offers a conceptual history of how people living in eastern Uganda have sustained and changed their ways of thinking about wealth and poverty over the past two thousand years. This history serves as a powerful reminder that colonialism and capitalism did not introduce economic thought to this region and demonstrates that even in contexts of relative material equality between households, people invested intellectual energy in creating new ways to talk about the poor and the rich. Stephens uses an interdisciplinary approach to write this history for societies without written records before the nineteenth century in which she reconstructs the words people spoke in different eras, using the methods of comparative historical linguistics, overlain with evidence from archaeology, climate science, oral traditions, and ethnography. Demonstrating the dynamism of people's thinking about poverty and wealth in East Africa long before colonial conquest, Stephens challenges much of the received wisdom about the nature and existence of economic and social inequality in the region's deeper past"--